2020
DOI: 10.33225/jbse/20.19.06
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Attitude Scale for Physics Courses and a Review of Student Attitudes

Abstract: The aim of present research was to develop a Likert type scale that determines the attitudes of 9th grade students towards physics courses so as to identify the physics students’ attitudes towards this course. The research started with a draft scale of 30 items. The draft scale was applied to 177 ninth grade students as a pilot research. According to results obtained from factor analysis, a scale that has 21 items and covering six sub-sets was developed. KMO value of the scale was .82; the Bartlett’s test valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The findings show that students' attitudes and beliefs about physics are influenced by differences in gender and personality [18,27], class level [11,28], type of school [9], and age [14,31]. Several findings state that male students have higher attitudes and beliefs than female students.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The findings show that students' attitudes and beliefs about physics are influenced by differences in gender and personality [18,27], class level [11,28], type of school [9], and age [14,31]. Several findings state that male students have higher attitudes and beliefs than female students.…”
Section: Results and Analysismentioning
confidence: 99%
“…22 [28] The respondents of this study were From this research it was found that the type of high school 460 students of class IX SMA affects attitudes towards physics subjects. Meanwhile, gender in downtown Nizip, Gaziantep and parental education level did not have a significant effect on province.…”
Section: [27]mentioning
confidence: 96%
“…Numerous tools exist for measuring physics learning. These predominantly focus on conceptual understanding and attitudes towards the subject (Brundage & Singh, 2023;Gürler & Baykara, 2020;Hestenes et al, 1992;Marake et al, 2022;Maloney et al, 2001). However, specialised instruments for measuring complex physics problem-solving abilities are less common (Adams, 2015).…”
Section: Instrument and Proceduresmentioning
confidence: 99%